Microsphere Assemblies via Phosphonate Monoester Coordination Chemistry. Issue 7 (16th January 2018) - Bladek, Kamila J.; Reid, Margaret E.; Nishihara, Hirotomo; Akhtar, Farid; Gelfand, Benjamin S.; Shimizu, George K. H.
Abstract: By complexing a bent phosphonate monoester ligand with cobalt(II), coupled with in situ ester hydrolysis, coordination microspheres (CALS=CALgary Sphere) are formed whereas the use of the phosphonic acid directly resulted in a sheet‐like structure. Manipulation of the synthetic conditions gave spheres with different sizes, mechanical stabilities, and porosities. Time‐dependent studies determined that the sphere formation likely occurred through the formation of a Co 2+ and ligand chain that propagates in three dimensions through different sets of interactions. The relative rates of these assembly processes versus annealing by ester hydrolysis and metal dehydration determine the growth of the microspheres. Hardness testing by nanoindentation is carried out on the spheres and sheets. Notably, no templates or capping agents are employed, the growth of the spheres is intrinsic to the ligand geometry and the coordination chemistry of cobalt(II) and the phosphonate monoester. Abstract : Micron‐scale coordination spheres are formed without any templates or capping agents by using phosphonate monoester linkers with a bent geometry.